Anguilla bicolor McClelland - Morgan, David L.; Allen, Gerald R.; Pusey, Bradley J.; Burrows, Damien W. (Zenodo, 2011)
Anguilla bicolor McClelland Indian Short-finned Eel Within Australia, this species is known only from the Kimberley and Pilbara (Indian Ocean Drainage Division, see Fig. 1) (Morgan & Gill 2004). The Kimberley distribution is sporadic (Fig. 4), with few specimens in the WAM and single site records during each of the studies by Allen (1975), Hutchins (1981), Morgan et al . (2002, 2004a) and Storey (2003) (Fig. 4). Within the Kimberley, A. bicolor is known from the Fitzroy, Prince Regent and Ord Rivers, and it has also been collected in Crystal Creek (Admiralty Gulf) and in Doubtful Bay (WAM records). Anguilla bicolor is also found in Tunnel Creek (May River) (Morgan, unpublished data). The sporadic distribution of A. bicolor throughout the Kimberley is probably a reflection of the number of natural barriers (waterfalls) that occur throughout the rivers of the region, which would limit the ability of the species to colonise many of its rivers. Published as part of Morgan, David L., Allen, Gerald R., Pusey, Bradley J. & Burrows, Damien W., 2011, 2816, pp. 1-64 in Zootaxa 2816 on page 10